The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00399-017-0517-z
|View full text |Cite
|
Sign up to set email alerts
|

A review of the atrial upper rate algorithms of St. Jude Medical (Abbott) cardiac implantable electronic devices

Abstract: This review focuses on the manifestations of the three triggered atrial upper rate functions of St Jude Medical cardiac implantable electronic devices. The occurrence of repetitive nonreentrant ventriculoatrial synchrony (RNRVAS) is also evaluated as a basis for the development of automatic mode switching (AMS) and as a trigger for atrial tachycardia/atrial fibrillation (AT/AF) event recordings. RNRVAS is a common trigger for AMS because all the atrial events or intervals are used to calculate the filtered atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Every episode started with an intrinsic P wave, which is consistent with the startup characteristics of AMS in the SJM (Barold, 2017). However, no atrial tachycardia was observed before any episode.…”
Section: Commentarysupporting
confidence: 79%
“…Every episode started with an intrinsic P wave, which is consistent with the startup characteristics of AMS in the SJM (Barold, 2017). However, no atrial tachycardia was observed before any episode.…”
Section: Commentarysupporting
confidence: 79%
“…RNRVAS was first described by Barold (1991). Several studies showed that in two‐chamber devices, long AV delay, long PVARP, short lower rate interval, presence of VA conduction and long VA conduction periods were predisposing factors of RNRVAS (Barold, 1991, 2017; Barold & Levine, 2001). A few studies described ventricular ectopic beats and retrograde atrial conduction after ventricular pacing as a trigger mechanism for RNRVAS (Barold, 1991; Sharma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These data prove RNRVAS is underreported and in fact more frequently encountered than currently estimated. In the ASSERT study, all the pacemakers were of St Jude Medical and atrial arrhythmia recognition algorithms of St Jude Medical devices are thought to be more sensitive in recognizing RNRVAS (Barold, 2017; Barold & Stroobandt, 2012; Kaufman et al, 2012). In St Jude Medical devices, AHRE algorithms use both sensed and paced atrial signal for recognition, therefore RNRVAS attacks are recorded as AHRE (Barold, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations